Transcriptomic and Metabolomic Approaches Deepen Our Knowledge of Plant–Endophyte Interactions - Chen, Xue-liang; Sun, Mei-chen; Chong, Sun-li; Si, Jin-ping; Wu, Ling-shang (Frontiers in Plant Science, 2022)
In natural systems, plant–symbiont–pathogen interactions play important roles in mitigating abiotic and biotic stresses in plants. Symbionts have their own special recognition ways, but they may share some similar characteristics with pathogens based on studies of model microbes and plants. Multi-omics technologies could be applied to study plant–microbe interactions, especially plant–endophyte interactions. Endophytes are naturally occurring microbes that inhabit plants yet do not cause apparent symptoms in them, and arise as an advantageous source of novel metabolites, agriculturally important promoters, and stress resisters in their host plants. Although biochemical, physiological, and molecular investigations have demonstrated that endophytes confer benefits to their hosts, namely in terms of promoting plant growth, increasing metabolic capabilities, and enhancing stress resistance, plant–endophyte interactions consist of complex mechanisms between the two symbionts. Further knowledge of these mechanisms may be gained by adopting a multi-omics approach. The involved interaction, which can range from colonization to protection against adverse conditions, has been investigated by transcriptomics and metabolomics. This review aims to provide effective means and ways of applying multi-omics studies to solve the current problems in the characterization of plant–microbe interactions involving recognition and colonization. The results obtained should be useful for identifying the key determinants in such interactions and would also provide a timely theoretical and material basis for the study of interaction mechanisms and their applications.